Handbook of polymer crystallization - Piorkowska, Ewa; Rutledge, Gregory Charles (Hoboken, New Jersey : Wiley, 2013)
"The only comprehensive reference on polymer crystallization, Handbook of Polymer Crystallization provides readers with a broad, in-depth guide on the subject, covering the numerous problems encountered during crystallization as well as solutions to resolve those problems to achieve the desired result."--Provided by publisher.
2.2 Conformation of Polymer Chains in Crystals and Conformational Polymorphism2.3 Packing of Macromolecules in Polymer Crystals; 2.4 Symmetry Breaking; 2.5 Packing Effects on the Conformation of Polymer Chains in the Crystals: The Case of Aliphatic Polyamides; 2.6 Defects and Disorder in Polymer Crystals; 2.6.1 Substitutional Isomorphism of Different Chains; 2.6.2 Substitutional Isomorphism of Different Monomeric Units; 2.6.3 Conformational Isomorphism; 2.6.4 Disorder in the Stacking of Ordered Layers (Stacking Fault Disorder); 2.7 Crystal Habits; 2.7.1 Rounded Lateral Habits; Acknowledgments.
Edition statement from first page of chapter PDFs.
Includes bibliographical references and index.
Print version record.
Keywords: Crystalline polymers; SCIENCE -- Chemistry -- Organic; Crystalline polymers; Ebooks -- UML; Electronic books